2015
DOI: 10.1063/1.4922746
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of time delay and scattering correlation functions in chaotic systems. I. Random matrix theory

Abstract: We consider the statistics of time delay in a chaotic cavity having M open channels, in the absence of time-reversal invariance. In the random matrix theory approach, we compute the average value of polynomial functions of the time delay matrix Q = −i ̵ hS † dS dE, where S is the scattering matrix. Our results do not assume M to be large. In a companion paper, we develop a semiclassical approximation to Smatrix correlation functions, from which the statistics of Q can also be derived.Together, these papers con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…It is worth emphasizing the different scalings of the variances with N : A systematic expression of the moments τ n W of the Wigner time delay for β = 2 was given more recently by Novaes [152]. We see that the variance diverges for N β 2, and the third cumulant for N β 4.…”
Section: Wigner Time Delay τ Wmentioning
confidence: 68%
“…It is worth emphasizing the different scalings of the variances with N : A systematic expression of the moments τ n W of the Wigner time delay for β = 2 was given more recently by Novaes [152]. We see that the variance diverges for N β 2, and the third cumulant for N β 4.…”
Section: Wigner Time Delay τ Wmentioning
confidence: 68%
“…(other references on time delay correlations are [31,43,16], and can also be found in the review papers quoted above). The joint distribution for the partial time delaysτ i 's and the diagonal matrix elements Q ii 's are still unknown.…”
Section: Chaotic Scattering In Quantum Dots and Random Matricesmentioning
confidence: 99%
“…The matrix generalisation of the latter approach to arbitrary N > 1 was presented in the influential work [36,37] by Brouwer, Frahm, and Beenakker (BFB) who showed that the proper time delays (more precisely, their inverses) are distributed according to the Laguerre ensemble of random matrices. This provided a route for applying powerful RMT techniques (like orthogonal polynomials and the Coulomb gas method) to study various densities, moments and correlators built on the Wigner-Smith matrix [21,44,45,46,47,48,49,50,51,52,53,54]. We refer to Ref.…”
Section: Perfect Coupling T =mentioning
confidence: 99%